Alam Pikir Masyarakat Madura yang Terepresentasikan Melalui Lagu Ta’ Andi’ Rokok (Cia-Cia) - Panakajaya Hidayatullah (Jurnal Kajian Seni, 2017)
Ta’ Andi’ Rokok (Cia-cia) is a Madurese dangdut song adaptated from Indian song entitledChaiyya-Chaiyya. The song lyrics are very infl uenced by the conception or perspective ofthe creator. This reasearch aims to understand paradigm of Madurese people representedthrough the song by using Foucault’s theory. The reasearch uses multidiscipline approachesby involving several different studies in order to reach comprehensive understanding.The research showsthat the Cia-cia song contains the discourse that consists of a groupof statements (speech) of debt and humour. Through the statements, the kinship andcharacteristic model of Madurese people may be taken as conclusion. Some discourse thenconstruct some dominant subjects which are,tarétan (cousins), kanca tatanggâ (neighbour),kanca main (friends), oréng teggâs (fi rm person), oréng sabbâr (patient person), humourist,and honest person. While some subordinate subjects are Bhâlâ Jâuh (extended family),moneylender, the other, oréng lécak (the indecisive), temperamental person, serious person,and deceitful.